Experimental study on fracture properties of steam-cured high-strength concrete - Xiaoqian Wang; Xinyang Li; Yuzhi Chen; Wenlei Xu; Xi Zuo (Materials Research Express)
To investigate the fracture performance of high-strength concrete (HSC) under different steam curing systems, this research conducted three-point bending tests on HSC and monitored the fracture process using acoustic emission (AE) and digital image correlation (DIC) technology. The experimental results indicate that both the delay period before steam curing and the duration of high-temperature steam curing have a significant impact on the strength and fracture performance of HSC. When the steam curing duration increased from 6 h to 12 h, the strength and fracture performance of the concrete initially improved and then declined. When the delay period was reduced from 4 h to 2 h, the strength and fracture performance exhibited a decreasing trend. The ratio of splitting tensile strength to compressive strength of HSC ranges from 1/10 to 1/12. The strain cloud map obtained through DIC technology revealed the development of cracks, and the variation in the length of the fracture process zone (FPZ) with the loading process was calculated. The activity of the HSC fracture process was reflected by the AE ringing count, and the damage evolution law of the fracture process was evaluated using the b -value. Shortened delay periods or excessive steam curing increased internal defects in HSC, leading to fracture via low-energy microcrack propagation. Properly cured HSC, with a denser microstructure, exhibited higher-energy failure along dominant fracture paths.